Microbial lithification in marine stromatolites and hypersaline mats - Dupraz, Christophe; Visscher, Pieter T. (My University, 2005)
Lithification in microbial ecosystems occurs when precipitation of minerals outweighs dissolution. Although the formation of various minerals can result from microbial metabolism, carbonate precipitation is possibly the most important process that impacts global carbon cycling. Recent investigations have produced models for stromatolite formation in open marine environments and lithification in shallow hypersaline lakes, which could be highly relevant for interpreting the rock record and searching for extraterrestrial life. Two factors that are controlled by microbial processes and physicochemical characteristics determine precipitation: exopolymeric substances and the saturation index, the latter being determined by the pH, {Ca2+} and {CO32−}. Here, we evaluate community metabolism in microbial mats and hypothesize why these organosedimentary biofilms sometimes lithify and sometimes do not.